ANALISIS PENGARUH STOCK SPLIT TERHADAP PERDAGANGAN SAHAM DI BURSA EFEK JAKARTA - Nurul Latifah P. (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2007)
A company in certain considerations can do split their stock into smaller nominal stock. This research is done purpose to learn the stock split impact in trading in companies which are listed in Jakarta Stock Exchange. The company's management purpose to do stock split for example to attract small investor interest and to raise stock liquidity